Fellow use of medical jargon correlates inversely with patient and observer perceptions of professionalism: results of a rheumatology OSCE (ROSCE) using challenging patient scenarios. Issue 8 (August 2016) - Berman, Jessica; Aizer, Juliet; Bass, Anne; Blanco, Irene; Davidson, Anne; Dwyer, Edward; Fields, Theodore; Huang, Wei-Ti; Kang, Jane; Kerr, Leslie; Krasnokutsky-Samuels, Svetlana; Lazaro, Deana; et al.
Abstract The NYC Rheumatology Objective Structured Clinical Examination (NYC-ROSCE) is held annually to assess fellow competencies. We recently redesigned our OSCE to better assess subspecialty trainee communication skills and professionalism by developing scenarios in which the patients encountered were psychosocially or medically complex. The objective of this study is to identify which types of verbal and non-verbal skills are most important in the perception of professionalism in the patient-physician interaction. The 2012–2013 NYC-ROSCEs included a total of 53 fellows: 55 MD evaluators from 7 NYC rheumatology training programs (Hospital for Special Surgery-Weill Cornell (HSS), SUNY/Downstate, NYU, Einstein, Columbia, Mount Sinai, and North Shore/Long Island Jewish (NSLIJ)), and 55 professional actors/standardized patients participated in 5 stations. Quantitative fellow performance assessments were made on the following: maintaining composure; partnering with the patient; honesty; professionalism; empathy; and accountability. Free-text comments were solicited regarding specific strengths and weaknesses. A total of 53/53 eligible (100 %) fellows were evaluated. MD evaluators rated fellows lower for professionalism than did the standardized patients (6.8 ± 0.6 vs. 7.4 ± 0.8, p = 0.05), suggesting that physicians and patients view professionalism somewhat differently. Fellow self-evaluations for professionalism (6.6 ± 1.2) were concordant with those of the MD evaluators. Ratings of empathy by fellows themselves (6.6 ± 1.0), MD evaluators (6.6 ± 0.7), and standardized patients (6.6 ± 1.1) agreed closely. Jargon use, frequently cited by evaluators, showed a moderate association with lower professionalism ratings by both MD evaluators and patients. Psychosocially challenging patient encounters in the NYC-ROSCE permitted critical assessment of the patient-centered traits contributing to impressions of professionalism and indicate that limiting medical jargon is an important component of the competency of professionalism.